ICCREM 2020 Intelligent Construction and Sustainable Buildings - Wang, Yaowu; Olofsson, Thomas; Shen, Geoffrey Q.P (American Society of Civil Engineers, 2020)
Proceedings of the International Conference on Construction and Real Estate Management 2020, held in Stockholm, Sweden, August 24-25, 2020. Sponsored by the Modernization of Management Committee of the China Construction Industry Association and the Construction Institute of ASCE.This collection contains 97 peer-reviewed papers on sustainable development in the construction industry and the advancement of intelligent construction theories and technologies.Topics include: intelligent construction and construction informatization; green construction and sustainable buildings; project management and construction industrialization; and construction industry and knowledge management.These papers will be of interest to researchers, engineering practitioners, developers, and planners from universities, consulting firms, and financial institutions.
Keywords: Sustainable development -- Congresses.; elektronické knihy; electronic books